Adaptive Reuse of Kotagede Museum Building As A Strategy For Preserving Kalang Houses in Yogyakarta - Pradnya Paramytha; Annanta Bayu Putra (Universitas Muhammadiyah Palembang, 2025)
Adaptive reuse is a building transformation through a new function without eliminating its original form and historical value, and is a strategy for sustainable preservation of cultural heritage buildings. One example of sustainable heritage preservation in the Special Region of Yogyakarta is the Kotagede Museum, located in a heritage area and housed in the historic Kalang House. This study examines the implementation of adaptive reuse in Rumah Kalang, a heritage house located in the cultural heritage area of Kotagede, which now functions as the Kotagede Museum. A descriptive qualitative method with a case study approach was employed. The findings reveal that the transformation from a private residence to a museum has preserved the building's physical character, despite the addition of new structures at the rear and functional changes in some spaces. The implications of this study indicate that adaptive reuse not only maintains the continuity of historical values and revitalizes spatial function but also reinforces the identity of the Kotagede heritage area.